Novel tetracycline hybrids: synthesis, characterization, docking studies and in-vitro evaluation of antibacterial activity - Mansi Shah; Bhanubhai Suhagia; Sunita Goswami; Sneha Sagar; Arpit Patwari (Future Journal of Pharmaceutical Sciences)
Abstract Background The biggest menace in the world today is the infection caused by pathogenic bacteria in humans, where majority of the available antibiotics fail to provide therapeutic results due to resistance. The discovery of new molecules is the need of the hour and several research groups worldwide are contributing to fight this scare. This work highlights our efforts towards discovering novel tetracycline hybrids that could serve as potent agents against several pathogenic bacterial strains causing infections. In total, ten compounds were synthesized which were chemically conjugates of Minocycline, an age-old tetracycline, and naturally occurring aldehydes and ketones available from the plant sources. Structural characterization of these compounds was done using Mass and 1HNMR. Molecular docking was carried out in order to predict the binding affinity of these compounds to various bacterial enzymes and known protein targets and to establish the structure–activity relationships. Molecular dynamic simulation studies and in silico pharmacokinetic and toxicity prediction studies were done to determine in silico pharmacokinetics and toxicity of compounds. In-vitro antibacterial activities were done using standard protocols against gram positive bacteria like Enterococcus faecalis, Staphylococcus aureus and gram-negative bacteria like Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli. Results Promising results were obtained viz. compound 1,2 and 10 were found to be more potent against Staphylococcus aureus, compound 1 against Enterococcus faecalis, compound 2 and 3 against Escherichia coli, compound 7 and 8 against Pseudomonas aeruginosa and compound 7 against Klebsiella pneumoniae when compared with minocycline as standard compound. Conclusion All the synthesized compounds were screened for their anti-bacterial activity against gram positive and gram negative microorganisms. Amongst the ten synthesized minocycline hybrids, four minocycline hybrids exhibited potent antibacterial activity as compared to minocycline. These hybrids can serve as a promising lead compound for antibiotic drug discovery.